A novel avionics based GNSS integrity augmentation system for manned and unmanned aircraft - Sabatini, Roberto (2017)
The aviation community has to implement very stringent navigation integrity requirements in a variety of manned and unmanned aircraft applications. This thesis presents the results of the research activities carried out by the Italian Air Force Research and Flight Test Centre (CSV-RSV) in collaboration with the Nottingham Geospatial Institute (NGI) and RMIT University in the area of Avionics Based Integrity Augmentation (ABIA) for mission-essential and safety-critical Global Navigation Satellite Systems (GNSS) applications in the civil/military aviation context. Space and Ground Based Augmentation Systems (SBAS/GBAS) have been developed in recent years to improve GNSS integrity, accuracy and availability for aircraft navigation and particularly for landing applications. SBAS satellites broadcast correction messages back to the earth, where suitably enabled receivers use the information to improve accuracy and integrity. The US, Europe and other nations have developed their own SBAS systems. In the US, the Wide Area Augmentation System (WAAS) exists and is operational. In Europe, SBAS coverage is provided by the European Geostationary Navigation Overlay Service (EGNOS), in Japan by the Multi-functional Satellite Augmentation System (MSAS) and India is developing the GNSS Aided Geo Augmented Navigation (GAGAN) system. An alternative approach to GNSS augmentation is to transmit integrity and correction messages from ground-based systems. An example is the American Local Area Augmentation System (LAAS), which allows a suitably equipped receiver to derive enhanced accuracy and integrity information in a local area. The combination of WAAS and LAAS is targeted to provide the Required Navigation Performance (RNP) in all phases of aircraft navigation, including en-route, terminal, approach/landing and surface operations. Along with SBAS and GBAS, GNSS augmentation may take the form of additional information being provided by other avionics systems. In most cases, the additional avionics systems operate via separate principles than GNSS and, therefore, are not subject to the same sources of error or interference. A system such as this is referred to as an Aircraft Based Augmentation System (ABAS). The additional sensors used in ABAS may include Inertial Navigation Systems (INS), TACAN/VOR-DME, Radar, Vision Based Sensors, etc. Unlike SBAS and GBAS technology, research on ABAS is limited and mainly concentrates on additional information being blended into the position calculation to increase accuracy and/or continuity of the integrated navigation solutions. Additionally, no significant attempts have been made of developing ABAS architectures capable of generating integrity signals suitable for safety-critical GNSS applications (e.g., aircraft precision approach and landing) and no flight certified ABAS products are available at present.